The Rise of Virtual Accounting Industry: Evidences from the Philippines - Norlito Moreno Dapiton; Jonathan C. Gano-an (Faculty of Economics, Universitas Sriwijaya, 2023)
When the working conditions changed due to lockdowns and social distancing protocols imposed by the government to prevent the spread of the COVID-19 virus, a lot of employees discovered opportunities to earn or make a living without leaving the safety and comfort of their homes. This paper aims to present a comparative analysis using descriptive quantitative research design that looks into the rise of the virtual accounting industry in the Philippines in the year 2019 to 2021 measured in terms of; the number of Filipino practitioners offering online accounting services, membership in exclusive social media groups for virtual accountants, published job openings for online accountants and potential income as broadcasted on social media and other available data. The paper relied on secondary data from pre-pandemic and post-pandemic phases, for the sake of establishing a rising trend. This paper also gathered primary information on some selected virtual accountants in the Philippines.